To survive the war - food troubles of the population of Bosnia and Herzegovina in 1917 - Užičanin, Salkan (Historical Thought, 2025)
The supply of food to the army and the civilian population during the First World War was a major problem for the Austro-Hungarian monarchy. Food shortages plagued the population of Bosnia and Herzegovina throughout the war, and the worst famine was in 1917. The pronounced problem with nutrition was a consequence of underdeveloped agriculture, which could not produce sufficient quantities of food even in peaceful times, so the deficit had to be imported. Although the authorities immediately after the outbreak of war took into their own hands the management of the most important articles of food, it quickly became clear that the supply and nutrition of the population would become one of the most important and difficult issues of the state. In the procurement of food and its distribution in the country through provisioning, the authorities faced numerous problems, such as insufficient and irregular transport, abuses, etc. However, its immediate consumers had the most trouble with provisioning. Due to the shortage of the most necessary foodstuffs, the population was forced to manage as best they knew how to survive. The most difficult situation, however, was in the passive parts of the country, where the people were dying of hunger.